Marco Aguilar, in Two Judgments by Jorge Debravo - Debravo, Jorge (2024)
With great literary and historical value, because of the close relationship between Marco Aguilar and the great poet Jorge Debravo, this article compiles two texts of this poet, with wise critical judgments, both written in different periods of time. The first text corresponds to the prologue of a poetry collection Cantos para la semana (Songs for the week) (1963), and the second to the introduction to a collection of poems by Aguilar, which was published in 1966 in the supplement Página Literaria, of La República Newspaper.